Ag-Doping Effect on MnO2 Cathodes for Flexible Quasi-Solid-State Zinc-Ion Batteries - Yanxin Liao; Chun Yang; Qimeng Xu; Wenxuan Zhao; Jingwen Zhao; Kuikui Wang; Hai-Chao Chen (Batteries, 2022)
Rechargeable aqueous Zn/MnO2 batteries are very potential for large-scale energy storage applications owing to their low cost, inherent safety, and high theoretical capacity. However, the MnO2 cathode delivers unsatisfactory cycling performance owing to its low intrinsic electronic conductivity and dissolution issue. Herein, we design and synthesize a Ag-doped sea-urchin-like MnO2 material for rechargeable zinc-ion batteries (ZIBs). Doping Ag was found to reduce charge transfer resistance, increase the redox activity, and improve the cycling stability of MnO2. The unique sea-urchin-like structure maintains rich active sites for charge storage. As a result, the Ag-doped MnO2-based ZIB presents a high reversible specific capacity to 315 mA h g−1 at 50 mA g−1, excellent rate performance, and a capacity retention of 94.4% when cycling over 500 cycles. An ex situ TEM test demonstrates the low-dissolution property of Ag-doped MnO2. A flexible quasi-solid-state ZIB is successfully assembled using Ag-doped MnO2 on graphite paper, which shows a stable specific capacity of 171 mA h g−1 at 1 A g−1 when cycled over 600 cycles. Our investigation demonstrates the significant role played by Ag doping in enhancing the ZIB performance of MnO2, and gives some insight into developing advanced active materials by heteroatom doping.